Summary Report on the Relationship between Juvenile Delinquency and Educational Environment - Sun, C. (Social Sciences and Childhood, 2024)
Abstract only This article explores the relationship between educational environment and the level of juvenile delinquency. The four main characteristics of juvenile delinquency are young age, low education level, organized structure of criminal groups, and high proportion of sexual crimes committed by offenders. The main factors causing juvenile delinquency are unequal family and social environment, educational environment, and access to quality education. The analysis of statistical data indicates an increase in the number of arrests of minors, highlighting the need for action. This article proposes suggestions for improving the educational environment and cultivating young people, aimed at preventing abnormal behavior. One of the central aspects of this article is the interaction between families, schools, and law enforcement agencies to comprehensively carry out the prevention of juvenile delinquency. Discussed the role of parents, the importance of incorporating legal education into schools, and labor education practices that promote social adaptation and sense of responsibility among young people. Статья посвящена взаимосвязям между образовательной средой и уровнем преступности среди несовершеннолетних. Выделяются четыре ключевые характеристики подростковой преступности: ранний возраст правонарушителей, низкий уровень образования, организованная структура преступных групп и высокая доля сексуальных преступлений. В качестве основных факторов, способствующих подростковой преступности, показаны семейное и социальное окружение, состояние образовательной среды и неравные возможности доступа к качественному образованию. Анализ статистических данных выявил увеличивающееся количество арестов среди несовершеннолетних, что подчеркивает необходимость принятия мер. В статье предлагаются рекомендации по улучшению образовательной среды и воспитанию молодежи, направленные на предотвращение девиантного поведения. Одним из центральных аспектов статьи является необходимость взаимодействия между семьей, школой и правоохранительными органами для комплексной работы по профилактике преступности среди несовершеннолетних. Рассматривается роль родителей, важность интеграции правового образования в школах и практики трудового воспитания, способствующие социальной адаптации и ответственности молодежи.